Role of Labor Unions in Enhancing Policy Learning in Health Insurance Expansion at the Local Level - Hanani, Retna; Naibaho, Samuel Martua; Sugiarto, Bowo (Journal of Transformative Governance and Social Justice, 2025)
This article examines the critical yet underexamined role of labor unions in facilitating policy learning for the implementation of Indonesia's National Health Insurance program (Jaminan Kesehatan Nasional, JKN) at the local level. Drawing on Bennett and Howlett's policy learning framework—instrumental, conceptual, and political—this study analyzes how unions transcend traditional advocacy to function as knowledge brokers in health policy adaptation. Based on qualitative data from interviews with 26 informants, including grassroots labor activists, union leaders, and representatives in formal policy bodies, the findings reveal three distinct contributions of unions to policy learning processes. First, unions facilitate instrumental learning through patient navigation systems, documentation of service variations, and technical feedback loops that identify implementation gaps. Second, they promote conceptual learning by reframing health insurance as a right, redefining implementation challenges as governance failures, and influencing public discourse. Third, they enable political learning through strategic alliance formation, sophisticated negotiation tactics, and leveraging electoral accountability mechanisms. The dynamic interaction between these learning types allows unions to serve as intermediaries between formal institutions and community experiences, enhancing JKN's responsiveness to citizen needs in a decentralized governance context. This study advances our understanding of how non-state actors can strengthen policy learning ecosystems and suggests that formal integration of unions into institutional learning processes could improve both the equity and sustainability of health coverage expansion in Indonesia and similar contexts.